2013
DOI: 10.1097/hjh.0b013e3283604176
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and cognitive function

Abstract: Objective An inverse relationship between blood pressure and cognitive function has been found in adults, but limited data are available in adolescents and young adults. We examined the prospective relation between blood pressure and cognitive function in adolescence. Methods We examined the association between BP measured at the ages of 12–15 years in school surveys and cognitive endpoints measured in the Seychelles Child Development Study at ages 17 (n=407) and 19 (n=429) years, respectively. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…With respect to the blood pressure, previous exploratory studies with sampling from general population revealed inconsistent results in investigating the association between blood pressure and cognitive performance. The finding of this study parallels recent evidence, in large adolescent populations, that there is no consistent association between BP and cognitive performance [ 17 , 42 ]. It is important to note that Lande et al [ 42 ] reported children with elevated systolic BP (SBP ≧ 90th percentile, n = 288) had lower average scores compared with normotensive children (SBP < 90th percentile, n = 4789) for digit span, block design, and mathematics in a nationally representative sample of 5077 children aged 6–16 years in the US (NHANES III).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…With respect to the blood pressure, previous exploratory studies with sampling from general population revealed inconsistent results in investigating the association between blood pressure and cognitive performance. The finding of this study parallels recent evidence, in large adolescent populations, that there is no consistent association between BP and cognitive performance [ 17 , 42 ]. It is important to note that Lande et al [ 42 ] reported children with elevated systolic BP (SBP ≧ 90th percentile, n = 288) had lower average scores compared with normotensive children (SBP < 90th percentile, n = 4789) for digit span, block design, and mathematics in a nationally representative sample of 5077 children aged 6–16 years in the US (NHANES III).…”
Section: Discussionsupporting
confidence: 90%
“…The result of this study shows no significant association between cholesterol level and cognitive abilities. A possible reason is that mild change in cardiometabolic risk factors may not be enough to trigger manifestations of cognitive decline [ 17 ]. A complex and dynamic network exists among cardiometabolic risk factors, cognitive abilities, and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…112 It may be that underlying physiological mechanisms linking hypertension and cognition may not be in play at such a young age. It is also possible that the tests used do not capture the variability in cognition that is associated with high BP at a young age.…”
Section: Hypertension and Cognition: Observational Studiesmentioning
confidence: 99%